The Saudi Arabian Economy Policies, Achievements and Challenges - Ramady, M. A.; SpringerLink (Online service) (Boston, MA : Springer US, 2005)
In this unique text, Mohamed Ramady develops a framework for studying fundamental challenges to the modern Saudi Arabian economy. Public and private sector topics include: . The hydrocarbon and minerals sector, including a new model of mining privatization and cooperation . The impact of small and medium sized businesses . The evolving role of "family" businesses . The growing role of women in the Saudi economy . Shifting trade patterns . The Saudi "offset" technology transfer program The author offers an analysis of key challenges facing the Saudi economy, including the potential costs and benefits of privatization, globalization, and eventual membership in the WTO. Employment, education, economic and social stability, and Saudi Arabia$1 (Bs place in the Gulf Cooperation Council are offered as keys to the consensus building needed to ensure the Kingdom$1 (Bs healthy economic future. Mohamed Ramady teaches in the Department of Finance and Economics, King Fahd University of Petroleum and Minerals. .s
The Setting -- Overview -- The Development Process -- Economic Planning: History, Role and Effectiveness -- Government Finances and the Saudi Budgetary System -- The Financial Markets -- Saudi Arabian Monetary Agency (SAMA) and Monetary Policy -- The Financial Markets -- The Saudi Capital Market -- The Domestic Sector -- The Private Sector: Challenges and Opportunities -- The Kingdom$1 (Bs Heart: The Hydrocarbon and Minerals Sector -- The Foreign Sector -- Foreign Trade -- The Saudi Economic Offset Program: A Tool for Technology Transfer -- Key Challenges -- Economic Liberalization: Globalization, Privatization and Foreign Direct Investment -- Population and Demographics: Saudization and the Labor Market -- Education and Knowledge for Development -- Saudi Arabia and the Gulf Cooperation Council (GCC) -- Conclusion -- Conclusion: The Challenges Ahead.s
Keywords: Macroeconomics; International economics; Development economics; Regional economics; Spatial economics; Economics; Macroeconomics/Monetary Economics//Financial Economics; Development Economics; Regional/Spatial Science; International Economics; Electronic books